An Analysis Of Second-Semester Economic Management Students’ Difficulties In English Reading Comprehension At Batanghari University Jambi - Kartika Dewi (Universitas Mathla'ul Anwar Banten, 2026)
This study aims to analyze the reading comprehension difficulties experienced by second-semester Economic Management students at Batanghari University Jambi, identify the most difficult reading comprehension components, and explore the factors influencing these difficulties. This study employed a qualitative ethnographic design. Data were collected through a reading comprehension test consists of 30 multiple-choice items and a questionnaire consists of 30 item. The sample consisted of 16 students. The questionnaire was administered using Google Forms. The instruments focused on five reading comprehension components: vocabulary understanding, identifying main ideas, making inferences, identifying references, and finding specific The findings revealed that vocabulary understanding, identifying main ideas, and making inferences were the most difficult reading comprehension components. The questionnaire results showed that 56.3% of the students experienced difficulties in understanding vocabulary and frequently relied on dictionaries when reading English texts. Meanwhile, the reading comprehension test indicated an average score of 83.81, which was categorized as good. This study concludes that although students achieved a good average score on the reading comprehension test, they still experienced difficulties in understanding vocabulary, identifying main ideas, making inferences, recognizing references, and locating specific information in English academic texts. Vocabulary and inference were found to be the most challenging components of reading comprehension. The findings of this study are expected to provide useful insights for improving English reading instruction, particularly in English for Specific Purposes (ESP) courses for Economic Management students